Adsorption of Pb(II)/benzohydroxamic acid collector complexes for ilmenite flotation. (September 2018) - Fang, Shuai; Xu, Longhua; Wu, Houqin; Tian, Jia; Lu, Zhongyuan; Sun, Wei; Hu, Yuehua
Highlights: Flotation performance of Pb(II)/benzohydroxamic acid complexes is investigated. Collection properties of these complexes depend on their chemical composition. Pb(II)/benzohydroxamic acid complexes exhibit high affinities to ilmenite surface. The studied complexes adsorb on ilmenite surface stronger than their components. Abstract: In this work, the flotation performance of separately added Pb 2+ ions and benzohydroxamic acid (BHA) was compared with that of Pb 2+ /BHA (Pb-BHA) complexes, and the possible adsorption mechanism on the ilmenite surface was investigated by conducting single-mineral flotation tests as well as zeta potential, ultraviolet (UV) spectroscopy, microcalorimetry, Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) analyses. The results of mineral flotation testing revealed that Pb-BHA complexes exhibited better flotation characteristics as compared to those of their sequentially dosed components, while the collection properties of these complexes depended on their compositions. Thus, the complexes with Pb 2+ /BHA molar ratios equal to 1:2 and 1:1 exhibited much higher ilmenite collection efficiencies and wider effective pH ranges than those of the complexes with Pb 2+ /BHA ratios of 2:1 and 3:1. Furthermore, the obtained zeta potentials indicated that the resultant Pb-BHA complexes with a Pb 2+ /BHA molar ratio of 1:1 were slightly positively charged. After increasing its magnitude, the zeta potential of ilmenite shifted toward positive values. Large amounts of Pb 2+ ions in solution were possibly adsorbed on the surface of ilmenite, which suppressed the adsorption of Pb-BHA species. The obtained UV spectra showed that varying the Pb 2+ /BHA ratio strongly affected the compositions of the produced complexes. The results of microcalorimetry analysis indicated that the adsorption heats (−Δads H) of the utilised reagents could be ranked in the order of Pb 2+ < BHA < Pb-BHA, suggesting that Pb-BHA species exhibited the highest affinities to the ilmenite surface. Finally, the obtained FTIR and XPS spectra revealed that Pb-BHA complexes were adsorbed on the ilmenite surface more strongly than their individual components.